Effect of boswellia and Lanolin Ointment on pain intensity of nipple in Lactating Women: A Randomized Clinical Trial - Masoumeh Mobaraki; Nahid Golmakani; Roshanak Salari; Seyed Reza Mazloum; Masoumeh Mirteimouri (Mashhad University of Medical Sciences, 2019)
Introduction: The prevalence of nipple pain is reported to be 34-96% which is among the common causes of early breastfeeding stopping. Lanolin is the recommended treatment to improve nipple pain. The anti-inflammatory and analgesic properties of boswellia have been approved. Therefore, this study was performed with aim to determine the effect of boswellia and lanolin ointment on nipple pain intensity in lactating women. Methods: This triple-blind randomized clinical trial was performed in 2018 on 68 lactating women with pain intensity of > 3 in pain visual scale in Mashhad. The subjects were placed in two groups of lanolin and boswellia ointment. The correct method of lactation and drug use were taught to the two groups. The score of nipple pain was recorded by the researcher before the intervention, on day three and eight after the intervention. Data were analyzed by SPSS software (version 21) and T, Fisher, Chi-square and Wilcoxon statistical tests. P<0.05 was considered statistically significant. Results: Before the intervention, mean pain severity in the two groups of lanolin and boswellia ointment was not significantly different (P = 0.23). On the seventh day after the intervention, mean pain severity was not significantly different in the two groups of lanolin and boswellia ointment (P = 0.40). But on the third day, mean of pain severity was significantly different between the two groups of lanolin and boswellia ointment (p <0.001) and pain intensity was lower in boswellia group than lanolin group. In intra-group comparison, mean pain intensity after the intervention (3rd and seventh day) was lower than the pre-intervention stage, which was statistically significant (P <0.001). Conclusion: Boswellia ointment and lanolin are same effective in reducing nipple pain.